The Effect of Bee Venom Acupuncture into Chok-samni (ST36) on Neuronal Activity in the Spinal Cord - Yim Yun-Kyoung; Kang Sung-Keel; Choi Do-Young (Korean Pharmacopuncture Institute, 2000)
This study was designed to evaluate the analgesic effect of bee venom (BV) Acupuncture into different treatment points, Chok-samni (ST36) and blank loci of the gluteal muscle and back. We investigated neuronal activity in the spinal cord using the Fos immunohistochemical technique according to the pretreatment with different concentrations of BV, thirty minutes before the formalin injection. The results were summarized as follows: 1. The number of Fos-like immunoreactive (Fos-LI) neurons in L2 segment of the saline-formalin treated group was significantly increased in NECK and VENT of the spinal cord as compared with that of the room control group. However, there was no significant change in the number of the Fos-LI neurons in L2 segment of the BV-formalin treated group as compared with that of the room control group. 2. The number of Fos-LI neurons in L3-5 segment of the saline-formalin group was significantly increased in all the regions of the spinal cord as compared with that of the room control group. However, the Fos-LI neurons in L3-5 segment of the BV-formalin treated group was dramatically decreased in all the regions of the spinal cord as compared with that of the saline-formalin group. Therefore, these results indicated that the BV acupuncture suppressed the nociceptive neuronal activities in L3-5 of the spinal cord induced by formalin injection. 3. There was a strong positive correlation between the formalin-induced pain behavior and the number of the Fos-LI neurons in L3-5 segment.